The Influence of Instructional Leadership, Learning Communities and Teacher Efficacy on Learning Quality - Dwi Haryono; Nurkolis Nurkolis; Titik Haryati (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to determine the effect of “instructional leadership, learning community, and teacher efficacy” on “learning quality’ in Madrasah Aliyah Swasta in Batang Regency. Utilizing a survey method, this study adopted a quantitative approach. All private Islamic senior high school (Aliyah Madrasah) teachers in Batang Regency formed the population for this research. From this population, a sample of 137 individuals was chosen using simple random sampling. A validated and reliable Likert scale questionnaire served as the data collection instrument. Then the data were analyzed by utilizing linear regression analysis. The results of data analysis show that partially and simultaneously, instructional leadership, learning community, and teacher efficacy have a positive and significant effect on learning quality. Instructional leadership applied by madrasah principals is able to encourage teachers to improve learning quality. An active learning community plays a role in strengthening collaboration and developing teacher professionalism. Meanwhile, high teacher efficacy contributes to the implementation of more effective and innovative learning. Thus, improving the quality of learning in Private Aliyah Madrasahs needs to be done through strengthening instructional leadership, fostering a dynamic learning community, and increasing teacher efficacy on an ongoing basis.